Learning Models in Islam (A Pragmatic Study) - Nurjanah; Agus Abdussalam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The article was written with the aim of pragmatically reviewing learning models in Islam. Learning in Islam emphasizes aspects of fostering spiritual and physical growth following Islamic teachings with the wisdom of guiding, teaching, training, maintaining and supervising the implementation of all Islamic teachings. It is deemed necessary to be understood wisely to bridge the success of educational goals. The research is written using a descriptive qualitative approach with a library research method. The ability to choose the right learning model for students is the duty and responsibility of an educator who has great hopes for the development of students' intellectual, emotional, and mental intelligence.